If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -3(x + 4) = 12 Reorder the terms: 9 + -3(4 + x) = 12 9 + (4 * -3 + x * -3) = 12 9 + (-12 + -3x) = 12 Combine like terms: 9 + -12 = -3 -3 + -3x = 12 Solving -3 + -3x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -3x = 12 + 3 Combine like terms: -3 + 3 = 0 0 + -3x = 12 + 3 -3x = 12 + 3 Combine like terms: 12 + 3 = 15 -3x = 15 Divide each side by '-3'. x = -5 Simplifying x = -5
| 2z/7+4=9 | | 0.2x+15.6=x-8.32 | | 25y+4=9 | | 0=X^2+4x-98 | | 825y+4=9 | | 12d+6y=57 | | P=(20+0.05x)+0.15(20+0.5x) | | x^2+y^2-x+2y+1=o | | 6/2=x/309.60 | | 8/8+8=9 | | 6/x=2/309.60 | | 3(x+2.25)=2x | | 5+6x=-2x-3 | | 5x-8+7=0 | | 42-2x=12-8x | | 0.4x+0.1=-19 | | 4/x=8/36.44 | | 4/x=8/$36.44 | | 8(x-7.8)=5.6 | | 24=12*2 | | 48=6 | | 7x+4.08=3x+10 | | 3t-6=4t+12 | | 8/10=12/x | | 3x+7=-28-4x | | (x-3)^2/3=0 | | a/6+8=11 | | 80=8*10 | | 10+5x=-6+x | | 8/12=x10 | | 10+5x=16x-54 | | t/6-4=10 |